The effect of forest stand characteristics on spider diversity and species composition in deciduous-coniferous mixed forests - Samu Ferenc (JOURNAL OF ARACHNOLOGY, 2014)
We studied how forest stand characteristics influence spider assemblage richness and composition in a forested region of Hungary. Deciduous-coniferous mixed forests dominate in the O˝rse´g National Park. Thirty-five plots were established and sampled for spiders for three years in 70–110 year-old stands with a continuum of tree species composition. Detailed background information was acquired for stand structure, tree species composition, forest-floor-related variables and spatial position of the plots. The effect of variables was analyzed by nonparametric multiplicative regression on rarefied spider species richness and by redundancy analysis on species composition. The relative importance of variable groups was assessed by variation partitioning. Spider species richness was positively and strongly affected by tree species richness, and the species composition of the spider assemblage was influenced by the proportion of the most important tree species. This study established the importance of tree species composition, but variance partitioning analysis also showed that tree species identity and forest floor variables together explain much of the variation. These findings may guide management and conservation efforts to maintain regional diversity of the spider fauna.